Penerapan model induktif kata bergambar untuk meningkatkan kemampuan membaca mata pelajaran bahasa indonesia kelas II SDI NW Lendang Bunga - Husairi, Husairi; Suhaeli, Siti (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2023)
This study aims to determine whether there is an increase in students' reading skills through the application of an inductive model of pictorial words in improving reading skills in Indonesian language class II SDI NW Lendang Bunga. The method used in this study was the researcher using Classroom Action Research method. The data collection techniques in this study were observation, documentation, and interviews. The research instruments were observation and documentation sheets. Observation sheets are direct observations in research and documentation are written items such as magazines, documents, and others. The results obtained in this study using the pictorial word inductive model to improve the reading skills of grade 2 students of the Islamic elementary school Nahdlatul Wathan Lendang Bunga are that there was an increase in the reading ability of students who previously could read 18 out of 29 students, and after carrying out class action students' reading ability increased from 29 students who could read to a total of 25 people.